2012
DOI: 10.1590/s0100-204x2012000300020
|View full text |Cite
|
Sign up to set email alerts
|

Volatilização de amônia proveniente de ureia com zeólita natural

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos da adição de zeólita a grânulos de ureia e dos diâmetros de grânulos nas perdas de NH 3 por volatilização e na absorção de N pelo sorgo. Formulações de ureia com adição de zeólita e ligante orgânico, nos diâmetros menores que 2 mm, 2-4 mm e maiores que 4 mm e, sulfato de amônio e ureia-NBPT, foram aplicados à superfície do solo sobre bandejas, em casa de vegetação. A adição de zeólitas naturais à superfície dos grânulos de ureia ou à composição destes di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…The urea sources associated both with zeolites and with urease inhibitor have proven efficiency in the literature regarding the reduction of nitrogen losses by volatilization when compared to the use of traditional urea (Pereira et al, 2009;Scivittaro et al, 2010;Werneck et al, 2012;Rech et al, 2017). In this way, the plant can absorb more nutrients, contributing to greater grain weight in these treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The urea sources associated both with zeolites and with urease inhibitor have proven efficiency in the literature regarding the reduction of nitrogen losses by volatilization when compared to the use of traditional urea (Pereira et al, 2009;Scivittaro et al, 2010;Werneck et al, 2012;Rech et al, 2017). In this way, the plant can absorb more nutrients, contributing to greater grain weight in these treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Werneck et al (2012) found that the association of zeolites with urea decreased the losses by volatilization by 20%, in addition to increasing the nitrogen uptake by the plants. Bernardi et al (2010) found satisfactory results with the use of ureaassociated zeolites in the oat crop, evidenced by the increased agronomic efficiency of nitrogen.…”
Section: Introductionmentioning
confidence: 97%
“…And more recently Campana et al [44] carried out a greenhouse pot experiment and a field trial with Tanzania Clinoptilolite is the most known and used zeolite specie for retaining ammonium cation [31]. Werneck et al [45] achieved reduction of losses by ammonia volatilization when urea was applied with clinoptilolite. The natural zeolites recovering or fully in the urea granule decrease on average the losses of NH 3 -N volatilization by 20%, and also increased the amount of the N absorbed by plants of sorghum.…”
Section: Results Of Field and Laboratory Studiesmentioning
confidence: 99%
“…Urea is the fertilizer that has had more problems with the topdress soil due to N losses through volatilization of NH 3 (Martha Jr. et al, 2004, Duarte et al, 2007, Werneck et al, 2012Nascimento et al, 2013). Nevertheless, this source is considered one of the most important due to its relative low cost, high water solubility and good absorption of the products of its hydrolysis by plants.…”
Section: Introductionmentioning
confidence: 99%